Changes in Student Conception About Water Dissolves Various Types of Substances Through POE Strategies assisted KIT Experiment Properties of Water (International Conference on Elementary Education, 2018)
As a result of interaction with various everyday phenomena, students often have alternative conceptions that are not in accordance with scientific conceptions. One of the concepts in the theme of water is water dissolving various substances. This study aims to identify changes in elementary school students' conception of the concept. This research uses descriptive method. The study involved 16 fifth graders at one of the schools in the city of Bandung. Students obtain a POE (Predict-Observe-Explain) learning strategy assisted by KIT to experiment with the properties of water. The research instruments included prediction questions (answered by students before the experiment), observation questions (answered by students after observing the experiment, and six-tier diagnostic tests (answered after receiving a scientific explanation from the teacher). The collected data were processed quantitatively to describe the conception of the students The results showed that the experimental observation activities and teacher explanations could increase the number of students who understood the scientific conception of the concept that water dissolved various substances, indicating that the POE assisted learning strategy of KIT experiments properties of water can improve mastery of concepts.